Teacher’s Perception of Duolingo for Vocabulary Learning in Inclusive EFL Classroom: A Qualitative Case Study - Zahwa Nazhifah Limbeng; Deasy Yunita Siregar (FOSTER: Journal of English Language Teaching, 2026)
The integration of digital learning applications has gained increasing attention in English language teaching, including in inclusive classrooms. While Duolingo has been widely used to support language learning, less attention has been given to how teachers perceive its use for vocabulary learning in inclusive classroom practice. Using a qualitative case study design, this study aimed to explore an English teacher’s perception of using Duolingo for vocabulary learning in an inclusive classroom and to identify the challenges encountered during its implementation. The study involved one English teacher at a junior high school in North Sumatra. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldana (2014). The findings revealed that Duolingo was perceived as a beneficial learning medium that supported vocabulary learning, increased students’ motivation, encouraged classroom participation, and facilitated the involvement of a slow learner student. However, differences in students’ learning abilities, the need for continuous teacher assistance, and technical constraints remained challenges during implementation. The study concludes that Duolingo’s effectiveness in inclusive classrooms depends on both the application and the instructional support provided throughout the learning process. These findings contribute to the growing discussion on technology integration in inclusive EFL classrooms by highlighting the importance of teacher scaffolding in maximizing the benefits of Mobile-Assisted Language Learning (MALL).